Epistemology of Pundhen Telaga Sarangan: A Study of Sacred Rites as Cultural Identity in Magetan, Indonesia - Setiyani, Wiwik; Nurhairunnisa, Nurhairunnisa; Holilah, Holilah (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2024)
This qualitative research tried to look at the origin of Pundhen Telaga Serangan as the epistemology of Islamic studies and the systematic transformation process of local tradition into cultural identity. Pundhen, in Javanese philosophy, has sacred meaning and magical power. Indonesians have a unique way of honouring and respecting their history. One of them is by performing rituals. Ancestors carried out the oldest practice for generations, and it became a custom. This paper uses qualitative methods, where the data collection techniques include interviews, documentation, and data qualification. Moreover, the Sarangan community in Magetan Regency is the object of this study because they have experienced cultural transformation. J.G. Frazer and E.B. Taylor's animistic and magic theory become analytical tools in seeing the extent of the meaning of Pundhen ontologically and epistemologically. Furthermore, Rudolf Bultmann's hermeneutical approach will serve as a valuable addition to the comprehensive analysis of this research. The results section of this research paper shows that Pundhen Telaga Sarangan is a symbol of spirituality. It is a sacred place for the locals to establish interpersonal relationships with God, ancestors, and spirits (the others).